Building entrepreneurial ecosystems: the case of Coimbra - Santos, Domingos (2022)
The purpose of this paper is three-fold. The first objective is to contextualize and clarify the concepts of regional innovation systems and entrepreneurship, addressing their differences and complementarities and suggesting an analytical filter to enhance their understanding. The second aim is to question and analyse the challenges this renewed approach brings to the domain of territorial policy, namely, the role it may bring to local and regional development strategies, opening up the way for a set of public policy interventions on the fields of entrepreneurship and innovation promotion. Finally, the paper presents and analyses the example of Coimbra, a medium-sized city in Portugal, underlining both the role of academia and the Instituto Pedro Nunes-Incubator have had on these domains.